2008
DOI: 10.1128/cvi.00129-08
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 Is Required for Development of Arthritis in Mice Vaccinated and Challenged withBorreliaSpecies

Abstract: We recently hypothesized that T helper 17 (Th17) cells and their associated cytokines are involved in the development of arthritis following infection with Borrelia burgdorferi. Here, we show that interleukin-23 (IL-23), a survival factor for Th17 cells, is required for the induction of arthritis in mice vaccinated with B. burgdorferi strain 297 and challenged with "Borrelia bissettii." When Borrelia-vaccinated and -challenged mice were given antibodies to the p19 subunit of IL-23, they failed to develop the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…It is a heterodimeric molecule composed of p40 and p19 subunits [3]. The proinflammatory activities of IL-23 are responsible for the onset not only of autoimmune diseases such as rheumatoid arthritis and multiple sclerosis [4,5], but also infection-induced pathological consequences of infection with the pathogens causing Lyme disease and toxoplasma encephalitis, for example [6,7]. The known biological roles for IL-23 in inflammation include induction of Th17-induced secretion of IL-17 [8] and suppression of CD4 + CD25 + Treg [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is a heterodimeric molecule composed of p40 and p19 subunits [3]. The proinflammatory activities of IL-23 are responsible for the onset not only of autoimmune diseases such as rheumatoid arthritis and multiple sclerosis [4,5], but also infection-induced pathological consequences of infection with the pathogens causing Lyme disease and toxoplasma encephalitis, for example [6,7]. The known biological roles for IL-23 in inflammation include induction of Th17-induced secretion of IL-17 [8] and suppression of CD4 + CD25 + Treg [9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, patients with BS-WA can fall within the spectrum of SpA, especially if they are positive for HLA-B27. The significance of folliculitis is still to be determined, since it is not necessarily associated with arthritis but is detectable in a relevant percentage of patients with BS-WA (87% in the group considered by Hatemi et al [5]). Larger cohorts of patients of different ethnic origins need to be examined in order to clearly define arthritis, assess SI joints and the enthesis with reproducible techniques such as MRI and US, and evaluate the association with HLA-B27.…”
mentioning
confidence: 98%
“…In their recent article, Hatemi and colleagues took the latter position (5). Using ultrasound (US) to evaluate the enthesis in Behçet's syndrome, the authors demonstrated an increased presence of enthesitis, a typical feature of SpA, in a subgroup of patients from Turkey with Behçet's syndrome with acne and arthritis (BS-AA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies with multiple animal models have shown that a Th1 response is not absolutely necessary for the development of arthritis after B. burgdorferi infection (9)(10)(11), while the inflammatory cytokine interleukin-17 (IL-17) contributes to disease (12)(13)(14)(15). Specifically, blocking IL-17 and various Th17-associated cytokines in vivo reduced the severity of arthritis observed in models of Borrelia-associated arthritis in the presence (15)(16)(17) or absence (12)(13)(14) of IFN-␥. Importantly, Infante-Duarte et al described the capacity of synovial cells of human Lyme arthritis patients to produce IL-17 when stimulated with B. burgdorferi microbes or lipoproteins (18).…”
mentioning
confidence: 99%